Towards Net Zero Energy Library Buildings - Selenay Aytac; Clara Tran (Issues in Science and Technology Librarianship)
This paper introduces the concept of “net zero energy,” presents some historical milestones through the idea of sustainability by reviewing the relevant literature, and highlights some case studies to strengthen the viewpoints on moving towards a sustainable future with net zero energy buildings. Many net zero energy buildings are being developed around the world, as well as in the United States’ communities, college campuses, and individual buildings. Libraries have also been supporting this initiative. For the next library renovation, librarians are encouraged to continue to leverage the net zero energy concept by developing net zero energy library buildings that produce their own renewable energy to meet the consumed energy demand, to safeguard a budget and energy-sustainable future.